Influence of Digit Sucking Habit on Masseter Muscle Thickness and Upper Airway Dimensions in Nigerian Children - Ada Njokanma; Olayinka Otuyemi; Kikelomo Kolawole (Nigerian Dental Association, 2023)
Background: Digit sucking habit (DSH) generates functional forces that can influence craniofacial morphology. Although the dental effects have been widely reported, its influence on the masseter muscle thickness (MMT) and upper airway (UA) dimensions is not well known.   Methods: Thirty (30) children selected from the orthodontic clinic (OAUTHC), with a DSH were matched with a group of 30 children without a DSH. Each group comprised of 16 males and 14 females. Ultrasonographic evaluation of the masseter muscle (MM) was performed to measure the left and right MMT in the relaxed and contracted states. Lateral cephalometric radiographs were obtained and 6 UA variables were measured on the x-ray. Data was analysed using SPSS version 20.0. Statistical significance was set at p<0.05. Inferential statistics was done using independent sample t test to compare means. Results: Participants in the DS group had a mean age of 7.7 ± 2.2 years, whereas those in the non-DS group had a mean age of 8.1 ± 2.1 years. The MM was generally thicker among the DS group, both in the contracted and relaxed states when compared with the non-DS group, but these differences were not statistically significant (p>0.05). The mean measurement of the width of the nasopharynx (P1) was significantly decreased among the DS group when compared with the non-DS group (p<0.05). There was no statistically significant difference in the mean values for the width of the oropharynx (P2), hypopharynx (P3), soft palate length (PNS-U1) and thickness (MPT) and the posterior bony boundary of the nasopharynx (PNS-Ba) between both groups. (p>0.05). Conclusion: Digit sucking habit caused a statistically significant narrowing of the width of the nasopharynx (p<0.05). The MMT did not differ significantly between the DS and non-DS groups both in the relaxed and contracted states.